2001
DOI: 10.1038/eye.2001.246
|View full text |Cite
|
Sign up to set email alerts
|

Corneal shape change during accommodation

Abstract: The study suggests that accommodation may have some effect on corneal shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…In the 1960s, no change in corneal shape was found to result from accommodation. 5,6 More recent studies found some change in corneal shape but the amount is small 7 and not in the central cornea. 8 The change in BFS, which was due to mydriasis, we found was different from that by Saitoh and colleagues.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the 1960s, no change in corneal shape was found to result from accommodation. 5,6 More recent studies found some change in corneal shape but the amount is small 7 and not in the central cornea. 8 The change in BFS, which was due to mydriasis, we found was different from that by Saitoh and colleagues.…”
Section: Discussionmentioning
confidence: 95%
“…They proposed that corneal steepening occurs when the ciliary muscles pull on the scleral spur, trabecular meshwork and the corneal limbus. Earlier studies 5,6 could not find significant corneal change with accommodation but recent studies have found that accommodation can affect the central 7 and mid-peripheral cornea. 8 Buehren and associates 8 using corneal topography proposed that significant cyclotorsion was found as a result of accommodation but no clear evidence of changes on corneal topography accounted for the torsional effect.…”
mentioning
confidence: 80%
“…Studies have found that accommodation of the lens can induce slight but measurable changes in the central corneal radius of curvature. 1 Subsequent studies have supported this 2 while others have shown that accommodation can produce changes in the shape and size of the globe. 3,4 Perhaps the most evident manifestation of ocular pliability throughout life is the development of myopia that is increasingly found to occur in adults.…”
Section: Introductionmentioning
confidence: 90%
“…Early studies, which were limited by the technology of the time, used optometers, keratometers, or photokeratoscopes to measure the cornea and suggest that little change in the cornea occurs with accommodation. [14][15][16][17] Pier scionek et al 18 used a modified keratometer to assess the effect of accommodation on central corneal shape and found that several subjects had a significant change in corneal curvature during accommodation; however, no definite trend toward steepening or flattening of the central cornea with accommodation could be demonstrated.…”
mentioning
confidence: 99%